1999
DOI: 10.1016/s0002-9440(10)65336-9
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Severity of the Glomerular Response to Nephron Reduction Is Strain-Dependent in Mice

Abstract: Nephron reduction is an important factor in the development of glomerulosclerosis. In a study of the oligosyndactyly (Os) mutation that causes a congenital 50% reduction in nephron number , we previously found that ROP Os/؉ mice developed glomerulosclerosis whereas C57B1/6J Os/؉ mice did not. We concluded that the predisposition to glomerulosclerosis depended largely on the genetic background , the ROP being sclerosis-prone whereas the C57 strain was sclerosis-resistant. In the current experiments we asked whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 18 publications
6
50
0
Order By: Relevance
“…We did not observe any glomerular changes in obese B-db3J mice. This is not surprising due to the lack of overt hyperglycaemia in these mice and the classification of the C57BL/6J strain as being resistant to developing glomerulosclerosis [44,45] using a completely different genetic model. Our results are interesting because LEPR-deficient C57BLKS/J-db mice, the parent strain of the F-db and the B-db strains, are hyperglycaemic and show signs of diabetic nephropathy with alterations in functional measures such as creatinine clearance [46].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any glomerular changes in obese B-db3J mice. This is not surprising due to the lack of overt hyperglycaemia in these mice and the classification of the C57BL/6J strain as being resistant to developing glomerulosclerosis [44,45] using a completely different genetic model. Our results are interesting because LEPR-deficient C57BLKS/J-db mice, the parent strain of the F-db and the B-db strains, are hyperglycaemic and show signs of diabetic nephropathy with alterations in functional measures such as creatinine clearance [46].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent works suggested that genetic factors influence the response to nephron reduction. Esposito et al (49) have shown recently that unilateral nephrectomy induced glomerulosclerosis in ROP, but not in C57BL/6 mice, whereas Kren and Hostetter (50) have reported that C57BL/6 mice were resistant to the devel-…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Os/ϩ ROP mice show that they possess approximately 50% fewer nephrons in the Os/ϩ mice than in the ϩ/ϩ mice (160). In general, wild-type mice (Os ϩ/ϩ , Ra ϩ/ϩ , and Pt ϩ/ϩ ) of ROP background seem to be more prone to glomerulosclerosis than C57BL/6 mice after a reduction in renal mass (161)(162)(163). Mice on the ROP background, in the absence of Os, Ra, or Pt mutant alleles, may also exhibit increased propensity for glomerulosclerosis after combined nephron mass reduction and diabetes (146).…”
Section: Ropmentioning
confidence: 99%